Kajian Pengembangan Sediaan Floating Sustained Release Tablet - Nazela Constantia Hilyatul Aulia; Sani Ega Priani; Ratih Aryani (UNISBA Press, 2022)
Abstract. Floating sustained release tablets were developed to increase the elimination half-life and bioavailability of the drug because it is able to release the active substance for a long duration by a floating mechanism in gastric fluid. This study aims to examine the development of floating tablets for the purpose of sustained release in terms of formulation and manufacturing methods, as well as the effect of developing floating sustained release tablets on pharmacokinetic parameters. The research method used is a systematic literature review by searching for international articles from reputable publishers. The results showed that floating sustained release tablet preparations had been developed for active substances such as alfuzosin HCl, baclofen, cephalexin, famotidine, imanitib mesylate, meberevine HCl, metformin HCl, and troxipide which had met the requirements of a good preparation, namely having a floating lag time in the range 5-600 seconds and a floating duration time of more than 12 hours. The most widely used manufacturing method is the effervescent with the addition of polymer and the presence of an effervescent , namely the reaction between sodium bicarbonate and organic acids (citric acid or tartaric acid). Floating sustained release tablets were able to increase the value of pharmacokinetic parameters such as t1/2, tmax and increase AUC in the range of 2.74-133.8%. Abstrak. Sediaan floating sustained release tablet dikembangkan untuk meningkatkan waktu paruh eliminasi dan ketersediaan hayati obat karena mampu melepaskan zat aktif dalam durasi yang panjang dengan mekanisme mengapung di dalam cairan lambung. Penelitian ini bertujuan untuk mengkaji pengembangan sediaan floating tablet untuk tujuan sustained release dalam hal formulasi dan metode pembuatan, serta pengaruh pengembangan sediaan floating sustained release tablet terhadap parameter farmakokinetik. Metode penelitian yang digunakan yaitu systematic literatur review dengan cara mencari artikel internasional dari penerbit bereputasi. Hasil penelitian ini menunjukan bahwa sediaan floating sustained release tablet sudah dikembangkan untuk zat aktif seperti alfuzosin HCl, baclofen, cephalexin, famotidine, imanitib mesylate, meberevine HCl, metformin HCl, dan troxipide yang dimana telah memuhi persyaratan sediaan baik yaitu memiliki nilai floating lag time dalam rentang 5-600 detik dan floating duration time lebih dari 12 jam. Metode pembuatan yang paling banyak digunakan yaitu metode effervescent dengan penambahan polimer serta adanya agen effervescent yaitu reaksi antara natrium bikarbonat dengan asam organik (asam sistrat atau asam tartarat). Sediaan floating sustained release tablet mampu meningkatan nilai parameter farmakokinetik seperti t1/2, tmax dan peningkatan AUC dalam rentang 2,74-133,8 %.